Participatory management in basic health units: a proposal to reinvent health work (Research, Society and Development, 2020)
This article aims to present an intervention proposal to reinvent management and work in primary health care, based on the implementation of collegiate managers in Basic Health Units. This is an action research with qualitative approach, developed in the municipality of Duque de Caxias, Rio de Janeiro. The methodological route was composed of three phases: exploration, planning and execution. The proposal was based on the wheel method, creating collective and concrete spaces for communication and permanent health education between managers and workers. It is hoped that this study can boost new research, new meanings and new possibilities for management and work in health services, producing new ways of doing health.